Strengthening arsenite oxidation in water using metal-free ultrasonic activation of sulfite. (October 2021) - Luo, Tao; Xu, Jing; Li, Jinjun; Wu, Feng; Zhou, Danna
Abstract: Although sulfite-based advanced oxidation processes (AOPs) have received renewed attention due to the production of oxysulfur radicals, the feasibility of using ultrasound (US) to activate sulfite remains unknown. In this work, low frequency ultrasound has been applied for the first time to develop a novel sulfite activation process (US–S(IV)) for enhanced oxidation of arsenite (As(III)). Our results showed that the US–S(IV) process with 1 mM sulfite addition and 20 kHz 650 W ultrasound can achieve approximately 2.9-fold increase in As(III) oxidation rate compared to the US process at pH 7. The mechanisms underpinning the US–S(IV) process have been probed through radical-scavenging experiments and electron spin resonance (ESR) spectrometry. Direct ultrasonolysis of sulfite has been demonstrated to be the predominant pathway producing the primary sulfite radical (SO3 ⁻) in the US–S(IV) process. Besides, the US-S(IV) process also works well in the treatment process of natural water, suggesting that this process could be promising in commercial scale application. This work not only provides a new application of ultrasound in sulfite-based AOP, but also provides further insights into how sulfite impacts the US process. Graphical abstract: Image 1 Highlights: Low frequency ultrasound (US) effectively activate sulfite (S(IV)). SO4 ⁻ played the most important role for arsenite oxidation in the US-S(IV) process. A thermal activation process for S(IV) happened in the US-S(IV) process. Dissolved oxygen (DO) and S(IV) consumption rate is low. Environmental matrices took minor impact on arsenite oxidation.